ANALISIS PENGARUH SISTEM MANAJEMEN KERJA TERHADAP TINGKAT KEBERHASILAN PRAKTEK KERJA LAPANGAN JURUSAN AKUNTANSI PADA SISWA SMK N 1 KOTA JAMBI - Andronikus, Dio; Kasiono, Kasiono (SJEE (Scientific Journals of Economic Education), 2021)
Abstract This study aims to determine: (1) Knowing how the description of the work management system and the success rate of field work practice in the accounting department at SMK Negeri 1 Jambi City. (2) Knowing how the work management system influences the success rate of field work practice in the accounting department at SMK Negeri 1 Jambi City. This research design uses quantitative research methods, with data collection techniques through questionnaires (questionnaire) and documentation. Where the population in this study were 146 students with a sample of 106 students. The research instrument test techniques used in this study were validity and reliability tests, while the classical assumption tests used were quantitative descriptive analysis, normality test, homogeneity test, simple regression test and partial t test. The results of this study indicate that: (1) There is a description between the implementation of field work practices and work management systems. (2) There is a significant influence between the work management system on field work practices in class XII accounting students at SMK Negeri 1 Jambi City. This is confirmed by t count> t table, which is 2.019> 1.658. Thus, the implementation of field work practices will be better implemented if the procedures and debriefing carried out by the school are optimized. The implementation of field work practices will be very influential if the process is guided by a good work management system. So, this linkage will have a better impact on the implementation of practical learning. Keywords: Work Management Systems, Street Vendors